Efectos de incrementar el intervalo entre entregas de agua bajo - Torres Ceja, Carlos de Jesús; Monreal Delgado, Brenda Catalina; Bárcenas Gómez, Iván Alejandro; Villamil Barriga, Carlos Wilcen (Acta Comportamentalia, 2015)